Health care without medicine: the impact of war on Sudan’s pharmaceutical manufacturing and supply - Aly Verjee; Thouiba Hashim Galad; Ruoh-Yeng Chang (Conflict and Health)
Abstract Background Armed conflict in Sudan since April 2023 has led to the widespread disruption of health care services, the destruction of public and private health care infrastructure nationwide, and the targeting of health care personnel. This study examines the impact of the conflict on a less publicized sector of Sudan’s health system: the national pharmaceutical manufacturing and supply chain. Methods Research interviews were conducted with representatives of 4 companies engaged in pharmaceutical manufacturing and/or supply in Sudan, in addition to a review of primary information from medical regulators and industry associations. Based on these interviews, 3 case studies are presented; insights from the fourth interview inform the study overall. Results All 4 companies reported significant impacts on their operations, as well as on other companies in the pharmaceutical sector. Domestic pharmaceutical manufacturing has effectively come to a halt, leading to the non-availability of certain drugs in parts of the country. Manufacturers have shifted course to focus on imports, but heavy losses of domestically stored inventory and an inability to distribute medicines to large parts of the country have had a significant impact on pharmaceutical supply to retail pharmacies, public and private sector health facilities, and the National Medical Supplies Fund (NMSF). Conclusions Sudan’s pharmaceutical manufacturing industry has been devasted. Although less visible than hospitals and medical personnel, the effects on the pharmaceutical sector are consequential for Sudan’s health sector, particularly for chronic conditions.